Altered Gut Microbiota and Plasma Metabolome Profiles Characterize Depression Individuals with Ischemic Stroke: A Comparative Analysis - Cao N; Lv D; Liu Y; Zhang H; Zhang X (Neuropsychiatric Disease and Treatment)
Ning Cao,1 Dongsheng Lv,2 Yanbin Liu,3 Huiru Zhang,4 Xingguang Zhang1 1School of Public Health, Inner Mongolia Medical University, Hohhot, Inner Mongolia, 010110, People’s Republic of China; 2Sleep Medicine Center, Mental Health Center of Inner Mongolia Autonomous Region, Hohhot, 010010, People’s Republic of China; 3Community Rehabilitation and Guidance Division, National Center for Mental Health, Beijing, 100013, People’s Republic of China; 4Cadre Healthcare Department, Mental Health Center of Inner Mongolia Autonomous Region, Hohhot, Inner Mongolia, 010010, People’s Republic of ChinaCorrespondence: Huiru Zhang, Cadre Health Section, Mental Health Center of Inner Mongolia Autonomous Region, Hohhot, Inner Mongolia, 010010, People’s Republic of China, Email 3651319814@qq.com Xingguang Zhang, School of Public Health, Inner Mongolia Medical University, Hohhot, Inner Mongolia, 010110, People’s Republic of China, Email zxg311@126.comPurpose: Depression has been recognized as a significant risk factor for ischemic stroke (IS). This study aimed to describe gut microbiota differences between depression people with and without IS, thereby establishing the link between gut microbiota and an elevated risk of IS development in people with depression.People and Methods: This study included 30 hospitalized patients with comorbid depression and IS, and 30 age-/sex-matched patients with depression alone. We used two approaches: (1) genetic analysis techniques (16S rRNA gene sequencing) to map gut microbial ecosystems, and (2) broad-spectrum chemical (nontargeted metabolomics) analysis to detect blood metabolites.Results: Alpha (α)-diversity and beta (β)-diversity of people with depression, with or without IS, did not show significant differences between the two groups. The IS group showed increased levels of gut bacteria carrying pro-inflammatory molecules, specifically Gram-negative Enterobacteriaceae containing lipopolysaccharide (LPS) components, the Linear discriminant analysis (LDA) value =4.177, P=0.014. Alongside, the IS group reduced populations of beneficial microbes that produce butyric acid important for gut health, such as Acidaminococcaceae (LDA value =4.045, P=0.014), Roseburia (LDA value =3.894, P=0.007), and Fusicatenibacter (LDA value =3.345, P=0.012), compared to the non-IS group. 38 plasma metabolites with significant differences between people with IS and non-IS groups. The abundance of Alloprevotella and Bacteroides massiliensis was correlated with 9 and 4 metabolites, respectively.Conclusion: This study highlighted that people with depression and IS exhibited distinct alterations in both their gut microbiome and metabolite profiles, in contrast to people with depression without IS. These findings may guide future interventions targeting gut microbiota to identify IS in depression people.Plain Language Summary: Depression has been identified as a significant risk factor for ischemic stroke (IS); this study aimed to describe gut microbiota differences between depression people with and without IS, thereby establishing the link between gut microbiota and an elevated risk of IS development in people with depression. This study included 30 hospitalized patients with comorbid depression and IS, and 30 age-/sex-matched patients with depression alone. We used two approaches: (1) genetic analysis techniques (16S rRNA gene sequencing) to map gut microbial ecosystems, and (2) broad-spectrum chemical (nontargeted metabolomics) analysis to detect blood metabolites. The results showed that people with depression and IS exhibited a higher prevalence of bacteria with lipopolysaccharide (LPS) structures and reduced presence of butyrate-producing bacteria. This study highlighted that people with depression and IS exhibited distinct alterations in both their gut microbiome and metabolite profiles, in contrast to people with depression without IS.Keywords: ischemic stroke, depression, gut microbiota, metabolome